Organic and inorganic bromine measurements around the extratropical tropopause and lowermost stratosphere: insights into the transport pathways and total bromine - Rotermund, Meike; Bense, Vera; Chipperfield, Martyn; Engel, Andreas; Grooß, Jens-Uwe; Hoor, Peter; Hüneke, Tilman; Keber, Timo; Kluge, Flora; Weyland, Benjamin; Schuck, Tanja; Vogel, Bärbel; et al. (Atmospheric chemistry and physics, 2021)
Abstract. We report on measurements of total bromine (Brtot) in the upper troposphere and lower stratosphere taken during 15 flights with the German High Altitude and LOng range research aircraft (HALO). The research campaign WISE (Wave-driven ISentropic Exchange) included regions over the North Atlantic, Norwegian Sea, and northwestern Europe in fall 2017. Brtot is calculated from measured total organic bromine (Brorg) added to inorganic bromine (Brinorgy), evaluated from measured BrO and photochemical modeling. Combining these data, the weighted mean [Brtot] is 19.2±1.2 ppt in the northern hemispheric lower stratosphere (LS), in agreement with expectations for Brtot in the middle stratosphere (Engel and Rigby et al., 2018). The data reflect the expected variability in Brtot in the LS due to variable influx of shorter lived brominated source and product gases from different regions of entry. A closer look into Brorg and Brinorgy, as well as simultaneously measured transport tracers (CO and N2O) and an air mass lag time tracer (SF6), suggests that bromine-rich air masses persistently protruded into the lowermost stratosphere (LMS) in boreal summer, creating a high bromine region (HBrR). A subsection, HBrR∗, has a weighted average of [Brtot] = 20.9±0.8 ppt. The most probable source region is air recently transported from the tropical upper troposphere and tropopause layer (UT/TTL) with a weighted mean of [Brtot] = 21.6±0.7 ppt. CLaMS Lagrangian transport modeling shows that the HBrR air mass consists of 51.2 % from the tropical troposphere, 27.1 % from the stratospheric background, and 6.4 % from the midlatitude troposphere (as well as contributions from other domains). The majority of the surface air reaching the HBrR is from the Asian monsoon and its adjacent tropical regions, which greatly influences trace gas transport into the LMS in boreal summer and fall. Tropical cyclones from Central America in addition to air associated with the Asian monsoon region contribute to the elevated Brtot observed in the UT/TTL. TOMCAT global 3-D model simulations of a concurrent increase of Brtot show an associated O3 change of −2.6±0.7 % in the LS and −3.1±0.7 % near the tropopause. Our study of varying Brtot in the LS also emphasizes the need for more extensive monitoring of stratospheric Brtot globally and seasonally to fully understand its impact on LMS O3 and its radiative forcing of climate, as well as in aged air in the middle stratosphere to elucidate the stratospheric trend in bromine.
Gesehen am 05.01.2022